Highly elastic and suturable electrospun poly(glycerol sebacate) fibrous scaffolds. (May 2015) - Jeffries, Eric M.; Allen, Robert A.; Gao, Jin; Pesce, Matt; Wang, Yadong
Graphical abstract: Abstract: Poly(glycerol sebacate) (PGS) is a thermally-crosslinked elastomer suitable for tissue regeneration due to its elasticity, degradability, and pro-regenerative inflammatory response. Pores in PGS scaffolds are typically introduced by porogen leaching, which compromises strength. Methods for producing fibrous PGS scaffolds are very limited. Electrospinning is the most widely used method for laboratory scale production of fibrous scaffolds. Electrospinning PGS by itself is challenging, necessitating a carrier polymer which can affect material properties if not removed. We report a simple electrospinning method to produce distinct PGS fibers while maintaining the desired mechanical and cytocompatibility properties of thermally crosslinked PGS. Fibrous PGS demonstrated 5 times higher tensile strength and increased suture retention compared to porous PGS foams. Additionally, similar modulus and elastic recovery were observed. A final advantage of fibrous PGS sheets is the ability to create multi-laminate constructs due to fiber bonding that occurs during thermal crosslinking. Taken together, these highly elastic fibrous PGS scaffolds will enable new approaches in tissue engineering and regenerative medicine.